Do Social Resources Protect Against Lower Quality of Life Among Diverse Young Adolescents?. (August 2016) - Scott, Sarah M.; Wallander, Jan L.; Elliott, Marc N.; Grunbaum, Jo Anne; Chien, Alyna T.; Tortolero, Susan; Cuccaro, Paula; Schuster, Mark A.
We examined whether social resources from the family and the community moderate the risk associated with low socioeconomic status (SES) for reduced quality of life (QL) among youth across racial/ethnic groups. Data were from 4, 824 fifth-grade youth (ageX ¯ = 11.1, SD = 0.6; 49% females) in the Healthy Passages™ study (2004-2006) located in Birmingham, Alabama; Los Angeles County, California; and Houston, Texas. Youth reported their QL using the Pediatric Quality of Life Inventory Version 4.0 and the Global Self-Worth subscale of the Self-Perception Profile and their status for hypothesized protective social mechanisms. Overall, family cohesion, parental nurturance, other adult, and peer support were positively associated with QL across racial/ethnic groups. There were few significant interactions, but all suggested that higher SES youth benefited more than lower SES youth. In fact, family cohesion among African American youth and other adult support among Hispanic youth differentiated QL at higher, but not lower SES. Further research should examine other risk contexts and seek to inform targeted prevention efforts.